Temporal Activity Patterns of the Spider Wasp Pepsis montezuma Smith (Hymenoptera: Pompilidae) in a Disturbed Lower Montane Rainforest (Manizales, Colombia) - Carlos Restrepo-Giraldo; Juanita Rodriguez; James P. Pitts (Psyche: A Journal of Entomology)
We studied the temporal activity pattern of the spider wasp Pepsis montezuma Smith (Hymenoptera: Pompilidae) in a disturbed lower montane rainforest, which is located in the city of Manizales, Colombia, at an altitude of 2,150 m. Females of this species are diurnal with two peaks of activity: one in the morning and the other in the afternoon. During the morning, nectar foraging occurred at Baccharis latifolia. During the afternoon, females hunted for tarantulas of the genus Pamphobeteus (Araneae: Theraphosidae), which were dragged backwards to the nest by the wasp. The nest was excavated before hunting. This is the first description of the behavior of Pepsis montezuma.